Slippery singularity studies: multidimensional performance as creation - Portovedo, Henrique (2022)
The intertwining of computation with artistic environments leads to a state of permanent articulation and supports the development of artistic creation. We are immersed in computation, living in a post- humanistic and post-digital world, in which it becomes fundamental to artistic practice, to artworks, and the aesthetic experience. Since the close of the twentieth century, there has been an outbreak of musical genres and musical expressions according to two principles: the integration of tradition and technological means; and the rupture of all the contexts that cannot be seen as directly deriving from the computer and digital technology. This means that the creation process trajectory goes from concrete realities towards an external space, based upon an understanding of the adaptation of the technical and technological realities to the needs of creation, while the creation process relies on an awareness of the technological potentialities as a means to attain an artistic result. Slippery Singularity Studies belongs to a series of pieces for multiple saxophones. These pieces were developed over the specialized algorithmic composition software named Slippery Chicken, which is written in and functions on the principles of the Common Lisp Object System (CLOS), the Common Lisp facility for object-oriented programming. These pieces for saxophone and electronics explore microtonal relations of tone pitches and layers of multiphonics permutations. The multiphonics were organised into layers of tremoli, producing timbral changes, and were selected through a process that uses two different methods and software. The first method was implemented through a patch named SaxMultis and allows the recording of all multiphonic timbral permutations and its cataloguing. It provides, as well, the possibility of random positions of key combinations for saxophone sounds. This software is organized in the following order: Selection of Key Position, Position of Tremolo, Indication of Dynamics, Creation of Buffer with positions code, Recording. The second method, Multi2Chord, is a software as well, which analyses the spectrum of each multiphonic permutation and translates it to musical notation using ZSA and BACH Max/MSP Libraries. Technology is moving faster than musical practices and we are taking some snapshots of techniques applied in musical composition and performance, techniques whose materialities will be quickly replaced by new ones, but whose embodied structures continue and become re-implemented in later technical objects as a recycling of skills. Understanding how emerging digital musical technologies trace their concepts, design and functionality to practices in the current cultural context will bring to light a study of new-media archaeology, conceptual epistles and performative paradigms, directed, in other words, to the study of how the new technologies of mixed music-making trace their design to the practices of material, symbolic, signal inscription and how practice is transforming and leading to creation.